(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
Declining crop yield due to weeds and their resistance to herbicides are major constraint for successful crop productions. Milk thistle (Silybum marianum) is common weed species in Australian cropping rotation. Allelopathic potentiality of milk thistle on different crops has been documented sporadically, but there is no literature on about ryegrass and canola. Therefore, a laboratory based allelopathic extracts bioassay was conducted. The hot water extracts was prepared from milk thistle plant parts added into water with ration of 1: 10 (plant sample: distilled water) where mixture was heated 10 minutes. After heat treatment samples was immediately sieved and centrifuged and the resulted solution was treated as 100% concentration. Separately, to get the fresh water extract plant sample was added into water (1:10) and kept 24 hours in room temperature. After 24 hours, the sample was sieved and centrifuged and collected samples result was treated 100% concentrations. To obtain 50% concentration, both hot and fresh samples were diluted with distilled water. Therefore the experiment was conducted with five different treatment concentrations (0, 50% hot water extracts, 50% fresh water extracts, 100% hot water extracts and 100% fresh water extracts). The experiment was comprised with RCBD design with three replications under control conditions. During experimental period the allelopathic effects of donor species on germination and seedling growth of ryegrass and canola was observed. Results shows, germination and seedling growth of both receiver species are inhibited by milk thistle extracts. Extracts from fresh water at 100% was more toxic to receiver species followed by 50% concentration of fresh and 100% from hot water extracts. This concentration reduced the root, shoot growth of ryegrass and canola 84.971%, 84.269% and 89.898%, 87.394%, respectively. The result also revealed that allelopathic pattern of hot water extracts was same however; it is less toxic to both receiver species. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.14007 Int. J. Agril. Res. Innov. & Tech. 2 (1): 62-67, June, 2012